Ectopic Expression of Retrotransposon-Derived PEG11/RTL1 Contributes to the Callipyge Muscular Hypertrophy - Xu, Xuewen (PLoS One, 2015)
The callipyge phenotype is an ovine muscular hypertrophy characterized by polar overdominance: only heterozygous + (Mat) /CLPG (Pat) animals receiving the CLPG mutation from their father express the phenotype. + (Mat) /CLPG (Pat) animals are characterized by postnatal, ectopic expression of Delta-like 1 homologue (DLK1) and Paternally expressed gene 11/Retrotransposon-like 1 (PEG11/RTL1) proteins in skeletal muscle. We showed previously in transgenic mice that ectopic expression of DLK1 alone induces a muscular hypertrophy, hence demonstrating a role for DLK1 in determining the callipyge hypertrophy. We herein describe newly generated transgenic mice that ectopically express PEG11 in skeletal muscle, and show that they also exhibit a muscular hypertrophy phenotype. Our data suggest that both DLK1 and PEG11 act together in causing the muscular hypertrophy of callipyge sheep.